2019
DOI: 10.1177/0883073819830193
|View full text |Cite
|
Sign up to set email alerts
|

Functional Neurologic Symptom Disorder in Children: Clinical Features, Diagnostic Investigations, and Outcomes at a Tertiary Care Children’s Hospital

Abstract: Objective: To describe the presenting symptoms and short-term outcomes of children diagnosed with functional neurologic symptom disorder and to compare the demographic and clinical characteristics of children who received neurodiagnostic testing to those who did not. Study Design: Single center, retrospective review of 222 children who presented to the emergency department of a children's hospital, and diagnosed with functional neurologic symptom disorder, between 2010 and 2015. Results: Out of 222 visits (fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…With an estimate of 12 new cases per 100,000 per year, FND disproportionately affects women compared to men (at 3:1) but the reported cases for men increases proportionately with age (Bennett et al, 2021). A 2019 study indicates that many pediatric patients were adolescent girls with seizure or stroke like symptoms (Watson et al, 2019). The adolescent age of this male patient in our case demonstrates deviation from these statistics.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…With an estimate of 12 new cases per 100,000 per year, FND disproportionately affects women compared to men (at 3:1) but the reported cases for men increases proportionately with age (Bennett et al, 2021). A 2019 study indicates that many pediatric patients were adolescent girls with seizure or stroke like symptoms (Watson et al, 2019). The adolescent age of this male patient in our case demonstrates deviation from these statistics.…”
Section: Discussioncontrasting
confidence: 54%
“…It is important to recognize the additional risk factors that can contribute to a patient's likelihood of developing FND. The identifiable triggers are often not of a catastrophic nature, despite common perception, and are more frequently related to family, school, or relationship conflicts (Watson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Resources pertaining to costs of FND for use in education and lobbying of administrators, government bodies, and insurance companies FND as a common disorder (approximately 16% of neurology outpatient visits and up to 23% of patients in epilepsy clinics) [43] , [44] . FND and other presentations with functional somatic symptoms are both common and costly [45] , [46] , [47] . Investment in recently developed treatment interventions (including those for functional seizures) is worthwhile because the interventions have good outcomes [48] , [49] , [50] .…”
Section: The Referral Process: Educational and Structural Interventions To Promote Changementioning
confidence: 99%
“…Consequently, the diagnosis is generally easier in younger children and much more complex in adolescents (Grattan-Smith and Dale, 2016). Again, as in the adult sample, studies about paediatric FND presentation (Guerriero et al, 2014), management (De Gusmão, et al, 2014; Watson et al, 2019) and neurobiological correlates (Kozlowska et al, 2017, 2018, 2019) have been conducted; however, little has been reported and quantified through rating scales with respect to the psychopathological features of FND in children and adolescents. This gap reflects the difficulties in the diagnostic approach to FND, especially in the paediatric population.…”
Section: Introductionmentioning
confidence: 99%